A new and efficient methodology for olefin epoxidation catalyzed by supported cobalt nanoparticles - Rossi-Fernández, Lucía; Dorn, Viviana; Radivoy, Gabriel (Beilstein Journal of Organic Chemistry, 2021)
A new heterogeneous catalytic system consisting of cobalt nanoparticles (CoNPs) supported on MgO and tert-butyl hydroperoxide (TBHP) as oxidant is presented. This CoNPs@MgO/t-BuOOH catalytic combination allowed the epoxidation of a variety of olefins with good to excellent yield and high selectivity. The catalyst preparation is simple and straightforward from commercially available starting materials and it could be recovered and reused maintaining its unaltered high activity.
Keywords: alkenes; cobalt nanoparticles; epoxides; oxidation; TBHP